Te frst record of Ficocyba fcaria (Horváth, 1897) (Hemiptera: Cicadellidae) in Russia - A.I. Gubin; V.V. Martynov; T.V. Nikulina (Кавказский энтомологический бюллетень)
Ficocyba ficaria (Horváth, 1897) (Hemiptera: Cicadellidae) is recorded for Russia for the frst time. Te material was collected in 2023–2024 on the Southern Coast of Crimea. This species has Mediterranean origin and is currently widespread in the south of Western Europe. Ficocyba ficaria exhibits a trophic association with honeysuckles (Lonicera spp.) and fg tree Ficus carica with obligatorily change of food plants throughout the year. The current distribution of the species and its harmfulness are discussed.